Hepatic haemangiomas: possible association with female sex hormones. Issue 9 (11th August 2004) - Glinkova, V; Shevah, O; Boaz, M; Levine, A; Shirin, H
Abstract : Background and aims: The association of hepatic haemangiomas with female sex hormones is not entirely clear. We prospectively evaluated the impact of female sex hormones on the natural history of liver haemangiomas. Methods: We followed 94 women with 181 haemangiomas diagnosed by ultrasound for a period of1–17 years (mean 7.3 (5.5) years). The location, number, size, and ultrasonographic pattern of the lesions were evaluated. Patients were also evaluated by questionnaire for gynaecological and reproductive history. We compared the change in number and size of haemangiomas in patients who received or did not receive exogenous hormonal treatment. Results: Age at first period was inversely associated with the size of haemangiomas ( r  = 0.181, p = 0.015) while age at menopause was positively correlated with the number of haemangiomas detected at first ultrasound ( r  = 0.542, p<0.0001). During follow up, no change in the ultrasonographic pattern or number of haemangiomas was observed. An increase in the size of the lesions was demonstrated in 5/22 (22.7%) hormone therapy exposed patients compared with 7/72 (9.7%) controls. Three variables (ultrasonographic pattern, number of haemangiomas, and hormone therapy) predicted whether or not a given haemangioma would increase in size. A hypoechoic pattern increased the risk of progression while a hyperechoic pattern decreases that risk (p = 0.003). The number of haemangiomas was inversely associated with the likelihood of progression (p = 0.006) and hormone therapy increased the risk of haemangioma enlargement (p = 0.05). Conclusions: Hepatic haemangiomas seem to be influenced by both endogenous and exogenous female sex hormones although significant enlargement occurs only in a minority of patients. Consequently, routine liver ultrasound follow up in women with hepatic haemangiomas receiving hormone therapy appears appropriate.